PROSES MANUFAKTUR PADA MESIN PRIMER DAN SEKUNDER CV. KARUNIA MENGGUNAKAN METODE LINIER PROGAMMING - Fauzi, Ahmad; Mas'ud, M. Imron (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2019)
Increasingly fierce business competition demands industries in manufacturing and services to increase the creativity of its business strategy. The same business strategy will not necessarily give the same results if it is still implemented so that its performance needs to be assessed. For this reason, companies are expected to be able to implement a good production process system and be able to continue to improve efficiency. CV. The gift is a company that moves coral (split) experiencing problems related to the determination of the number of products produced by the company every month. This causes that in each period, the company experiences excess - decreases in production so that the company's profit is not optimal and results in a large saving cost. This situation occurs because the company has been carrying out production planning based on intuition. The method used as a solution is Linear Progamming. This study aims to determine the production process and increase company profits. For the calculation of the amount of production in each period. Then it can be concluded that the objective function sought is the optimal value